PODCASTING FOR EDUCATION IN ENTEROSTOMAL THERAPY DURING THE COVID-19 PANDEMIC (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To describe the experience of nursing academics on the use of podcast for education in enterostomal therapy during the pandemic of COVID-19. Method: Experience report on health education activity held between June and October 2021, which describes the creation of a podcast channel and disclosure of contents in stomatherapy. Results: Sixteen episodes approached the three stomatherapy study areas, one containing the introduction, eight on wounds, four on ostomies and three on incontinences. Conclusion: Through the use of the podcast to disseminate contents in stomach therapy, the practicality and cost-benefit of technology to implement distance health education were observed.